Persepsi Siswa tentang Kompetensi Pedagogik Guru dalam Pengajaran Pendidikan Agama Islam di SMA Negeri 2 Sungai Limau - Utama, Andre Putra; Alfurqan, Alfurqan (ALSYS, 2024)
This research was conducted with the aim of obtaining information and describing teacher pedagogical competence. The data analysis technique in this research uses quantitative descriptive statistics. The population of this study was class XI students of SMA N 2 Sungai Limau, totaling 225 people, with a sample size of 45 people. Sampling used a simple random sampling technique. The instrument of this research is a Likert Scale model questionnaire. Before use, the questionnaire was first tested for validity and reliability. The collected material is processed by finding the average value. The research results show that pedagogical competence is seen from (1) Understanding of students with a score of 52% with fairly good criteria. (2) The design and implementation of learning received a score of 62% with fairly good criteria. (3) The use of learning technology received a score of 42% with poor criteria. (4) Evaluation of learning outcomes received a score of 62% on fairly good criteria. (5) Developing students' potential, getting a score of 55% with fairly good criteria. Based on the research results, it can be concluded that the pedagogical competence of teachers at SMA Negeri 2 Sungai Limau is at quite good criteria with an average score of 57.33%. This needs to be paid attention to in order to improve teachers' abilities so that teaching and learning activities can be carried out in sync with the plan and can achieve the expected goals.